Implementation Strategy of Fun English Educationin Approach SWOT Analysis - Andi Alfianto Anugrah Ilahi; Syahban Mada Ali (IECON: International Economics and Business Conference, 2023)
This study aims to determine the marketing strategy for the development of Fun English Education Course Institutions and find the right marketing strategy in implementing marketing mix which includes 4P (product, promotion, place, people) at Fun English Education Course Institutions to achieve targets using the SWOT Analysis approach. The method used is descriptive qualitative which can answer the problems that have been found by researchers and analyze the phenomena that occur in Fun English Education accompanied by a SWOT analysis to review the strengths and opportunities that the institution has andthen make maximum use of it to overcome the weaknesses and threats that arise. faced. After carrying out a SWOT analysis and formulating a new strategy, it turns out that Fun English Education in terms of development still has marketing strategy constraints from various sectors. For this reason, Fun English Education needs to maintain the strategy that has been successfully implemented and develop a more varied product differentiation and prioritize promotional activities to various schools on certain activities.